Implementation of Web-Based CBT Application in AIK Learning at Muhammadiyah Al-Kautsar PK School - Saputri, Intan Dian; Nurul Latifatul Inayati (Tadrib: Jurnal Pendidikan Agama Islam, 2024)
The development of information and communication technology has had a major impact on various fields including education. In Indonesia, digitalization aims to increase the effectiveness of teaching and learning processes and educational activities. Assessment using web-based technology, such as the Computer Based Test (CBT), is a solution that overcomes various obstacles to paper-based assessment. CBT allows assessments that reduce the risk of conditions and errors. This research uses a qualitative method that applies a phenomenological approach with observation, interviews and documentation as data collection techniques. Data analysis was carried out in four stages: data collection, data reduction, data presentation, and drawing conclusions. The research results show that the implementation of a web-based CBT application increases the efficiency and effectiveness of the learning and assessment process. However, there are several obstacles, such as limited technical abilities of teachers, technical problems related to software and internet connectivity, and the difficulty of including Arabic text in exam questions. Creative solutions such as converting Arabic text into images have helped overcome some of these problems. In addition, the CBT application features that support exam security and automatic data storage provide additional benefits. Overall, the implementation of the web-based CBT application at SMP Muhammadiyah Al-Kautsar PK Kartasura shows that this technology can optimize the learning and assessment process, but several existing obstacles still need to be overcome. With further improvements in infrastructure and teacher training, CBT can become an effective tool for improving the quality of education in Muhammadiyah schools.